Factors influencing the usage of zero single-use plastic by IIUM community - Yuhani, Nor Shafiqizni; Mohd Effendi, Nur Ashikin; Rushdan, Norsyaza Hanis; Zamri, Farah Nadira; Wok, Saodah (Centre of Research in Media and Communication, Universiti Kebangsaan Malaysia, 2019)
IIUM Zero Single-Use Plastic Campaign was launched in February 2019, requiring everyone in IIIIM not to use plastics including plastic straws, plastic bags, and plastic food containers. As such, this study attempted to gauge the IIUM community's reception towards the Zero Single-Use Plastic Campaign. The objectives of this study are: (1) to determine the level of awareness, perception, attitude, readiness, and behavior towards the Zero Single-Use Plastic Campaign; {Z)to analyze the relationship among awareness, perception, attitude, readiness, and behavior in the Zero Single-Use Plastic Campaign; and (3) to find out the best predictor of community behavior towards such campaign. The study tested the theory of planned behavior and employed a quantitative research design using the survey method with the questionnaire as its research inskument for data collection. A total of 398 respondents participated in the study. The results of the study shcw that there is a high level of readiness, awareness, perception, attitudg and behaviortowards the Zero Single-Use Plastic Campaign.. AIso, there are positive and significant relationships between factors and behavior (usage). Readiness is the best predictor of the zero single-use plastic usage. All the hypotheses are supported. Therefore, it can be ccncluded that the IIUM Campus community supports the campaign. Hence, the theory of plarmed behavior holds true.